2013
DOI: 10.4172/jcsb.1000103
|View full text |Cite
|
Sign up to set email alerts
|

In silico Analysis of Novel Mutation ala102pro Targeting pncA Gene of M. Tuberculosis

Abstract: This study reports on the structural and functional basis of pyrazinamide (PZA) resistance conferred by a novel mutation Ala102Pro in pncA gene as sequenced from a PZA resistant Mycobacterium tuberculosis strain. Molecular modeling studies of Wild Type (WT) and Mutant Type (MT) of Pyrazinamidase (PZase) showed the mutation at Ala102Pro does not impact on the conformation of the protein. However, the docking studies infer that MT has a higher inhibitory constant (Ki-990.0m) compared to WT (Ki-822.42m), which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Maximum 32 conformers were considered for PZA. A grid was generated using Schrodinger's Receptor grid generation application around the active site residues Cys138, Thr135, Ala134, Ile133, Lys96, His71, Trp68, Phe58, His57, His51, Asp49, Phe13, and Asp8 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maximum 32 conformers were considered for PZA. A grid was generated using Schrodinger's Receptor grid generation application around the active site residues Cys138, Thr135, Ala134, Ile133, Lys96, His71, Trp68, Phe58, His57, His51, Asp49, Phe13, and Asp8 …”
Section: Methodsmentioning
confidence: 99%
“…A grid was generated using Schrodinger's Receptor grid generation application around the active site residues Cys138, Thr135, Ala134, Ile133, Lys96, His71, Trp68, Phe58, His57, His51, Asp49, Phe13, and Asp8. 55,56 Extra precision docking protocol 57 was implemented. Total ligand-receptor interaction energy was calculated on the basis of van der Waals interaction forces, electrostatic energy and H-bond interactions within the ligand and receptor.…”
Section: Receptor-ligand Interactionmentioning
confidence: 99%
“…It is also possible that such mutation in the PZA binding pocket of PncA make the binding site more flexible, which allows the tight interactions between PncA mutant protein and the PZA drug that may affect the release of PZA from the binding pocket. Previous study has shown that such mutations cause the flexibility in ligand binding site that affect the drug binding …”
Section: Resultsmentioning
confidence: 99%
“…Previous study has shown that such mutations cause the flexibility in ligand binding site that affect the drug binding. 45…”
Section: Virtual Drug Screening Identified An Active Lead Compound Against Pyrazinamide Resistant M Tuberculosis Mutantsmentioning
confidence: 99%